Baruch and the Epistle of Jeremiah : a commentary based on the texts in Codex Vaticanus - Adams, Sean A. (Septuagint Commentary Series., 2014)
This work is the first major commentary of LXX Baruch and the Epistle of Jeremiah in English. Rather than seeing LXX mainly as a text-critical resource or as a window on a now-lost Hebrew text, this commentary, as part of the Septuagint Commentary Series, interprets Baruch and EpJer as Greek texts and from the perspective of Greek readers unfamiliar with Hebrew. Included are a transcription and an English translation of Codex Vaticanus, the oldest extant manuscript of the books, and a detailed commentary. Another major contribution is the utilisation of the sense-delimitation (paragraphs) of Codex Vaticanus and other codices to explore how early readers interpreted the text.